Software Engineering Methods in Intelligent Algorithms Proceedings of 8th Computer Science On-line Conference 2019, Vol. 1 - Silhavy, Radek (Advances in Intelligent Systems and Computing, 2019)
This book presents software engineering methods in the context of the intelligent systems. It discusses real-world problems and exploratory research describing novel approaches and applications of software engineering, software design and algorithms. The book constitutes the refereed proceedings of the Software Engineering Methods in Intelligent Algorithms Section of the 8th Computer Science On-line Conference 2019 (CSOC 2019), held on-line in April 2019. .